THE NETWORK TECHNOLOGY IN ORGANIZATION AND MANAGEMENT OF THE UNDERGRADUATES' INDEPENDENT WORK ON 'PEDAGOGICAL EDUCATION' PROGRAM - Tatyana Anatolyevna Shevchenko; Galina Ivanovna Kulikova; Aleksandr Ivanovich Shevchenko (Современная наука и инновации, 2022)
Activation of cognitive activities in the students' independent work can be intensified by means of organization and management of the educational process in principle. The diagnostics of the efficiency of students' independent work, assessed by the 'independence' and 'self-rating' indexes, can change students' attitude to the independent learning activities.